The Manifesto-Media Link: How Mass Media Mediate Manifesto Messages - Nicolas Merz (Humboldt-Universität zu Berlin, 2017)
This study analyzes whether media coverage covers messages from parties' electoral programs (manifestos). Electoral programs contain detailed information on a party's future policy-making. However, few voters read electoral programs. Still, prior research often assumed that the content of manifestos is known to voters because media disseminate the content of manifestos to voters. This dissertation evaluates this “mediation assumption” empirically, and analyzes whether and how the mass media cover parties' electoral programs during the electoral campaign. If media coverage did not reflect parties' electoral programs, citizens would have no chance to base their vote choice on evaluations of those programs. This study introduces the concept of the manifesto-media link in order to describe how media coverage can reflect programmatic offers. The manifesto-media link is formulated as three conditions that can be empirically evaluated and tested in a similar way to the conditions of the responsible party model. These are: First, media must cover similar issues to those that parties cover in their electoral programs. Second, media coverage must link issues with parties that emphasize these issues more than their competitors, in order to inform about the parties' issue priorities. Third, media must frame parties as left or right in a way that represents how parties emphasize left or right positions in their own manifestos. Methodologically, the study combines secondary content analytical data on media coverage during the electoral campaign with data based on electoral programs. The findings suggest that the manifesto-media link is stable and robust. There is little to no systematic bias in favor of a certain type of party, however there are differences between quality and tabloid media. These findings contribute to our understanding of political representation and the functioning of political competition. – – Diese Arbeit geht der Frage nach, inwiefern die Medien während des Wahl-kampfs über die Wahlprogramme der Parteien berichten. Die Wahlprogramme der Parteien enthalten Informationen darüber, was Parteien nach der Wahl vorhaben. Allerdings lesen wenige Wählerinnen und Wähler Wahlprogramme. Die vergangene Forschung über und mit Wahlprogrammdaten hat bisher angenommen, dass der Inhalt von Wahlprogrammen von den Medien verbreitet wird. Diese Doktorarbeit untersucht diese Annahme empirisch und analysiert, ob und wie Massenmedien während des Wahlkampfs über die Inhalte der Wahlprogramme berichten. Wenn Massenmedien nicht die Inhalte der Wahlprogramme verbreiten würden, hätten Bürgerinnen und Bürger kaum Chancen sich über das programmatische Angebot der Parteien zu informieren. In dieser Arbeit wird das Konzept des Manifesto-Medien-Links entwickelt. Das Konzept bringt Theorien des Parteienwettbewerbs und Theorien der Medienselektion zusammen. Der Manifesto-Medien-Link formuliert drei Bedingungen, welche empirisch getestet werden können. Diese sind: Erstens, Medienberichterstattung und Wahlprogramme müssen zumindest zu einem gewissen Grad dieselben Themen diskutieren. Zweitens, Journalisten müssen Sachfragen mit jenen Parteien verknüpfen, welche diese Themen in ihren Wahlprogrammen stärker betonen als ihre Konkurrenten, um Wählerinnen und Wähler über die Prioritäten der Parteien zu informieren. Drittens, Medien müssen die ideologische Orientierung einer Partei sowie Veränderungen dieser korrekt wiedergeben. Methodisch werden in der Arbeit Wahlprogramm- und Mediendaten kombiniert. Die Ergebnisse zeigen, dass der Manifesto-Medien-Link relativ stabil ist. Außerdem wird gezeigt, dass es nur geringe systematische Verzerrungen zugunsten bestimmter Parteien gibt. Jedoch zeigen sich Unterschiede zwischen Qualitäts- und Boulevardmedien. Die Ergebnisse haben Implikationen für unser Verständnis von politischer Repräsentation und den politischen Wettbewerb.
urn:nbn:de:kobv:11-110-18452/19591-8; Additional information: Dissertationsschrift / PhD Thesis, Humboldt-Universität zu Berlin, Kultur-, Sozial- und Bildungswissenschaftliche Fakultät, 2017
Keywords: 320; electoral programs; manifestos; mass media; media; media coverage; parties; political parties; Medienberichterstattung; Parteien; Medien; Sachfragen